Stakeholders Perceptions of a Universal Sustainability Assessment in Higher Education - Antonios Maragakis; Andy van den Dobbelsteen; Alexandros Maragakis (A+BE: Architecture and the Built Environment, 2018)
The progress of sustainability within higher education has steadily increased in focus over the last decade and has increasingly become a topic of academic research. As institutions investigate, implement and market sustainability efforts, there is a myriadof sustainability assessment methodologies currently available. This assortment of standards being used by institutions do not help students and faculty assess the level of sustainability uniformly between institutions.